Neutrophil-to-lymphocyte ratio (NLR) fails to predict outcome of diffuse large B cell lymphoma. (2019) - Azuma, Yoshiko; Nakaya, Aya; Fujita, Shinya; Satake, Atsushi; Nakanishi, Takahisa; Tsubokura, Yukie; Saito, Ryo; Konishi, Akiko; Hotta, Masaaki; Yoshimura, Hideaki; Ishii, Kazuyoshi; Ito, Tomoki; et al.
Abstract: Background: Neutrophil-to-lymphocyte ratio (NLR) has been recognized as a poor prognostic indicator in various solid tumors. Methods: We retrospectively analyzed 530 patients with de novo DLBCL who were diagnosed from April 2002 to November 2017. Results: The median age of patients was 69 (range, 20–95) years, and 59% were male. The optimal cutoff for NLR was 5.2. NLR (5.2) was not associated with overall and progression free survival. Conclusion: Our study failed to reveal the predictive value of NLR and demonstrated that the NCCN-IPI might be the most powerful predictor in DLBCL.